REACHING THE HORIZON WITH AN UNDERSTANDING OF THE IDEA OF HOLY IN ILLUMINATION OF RUDOLF OTTO - D’Souza, Romero Luciano (Asian Horizons, 2012)
Rudolf Otto (1869-1937), was born at Peine in Hanover in 1869. He was one of the German neo-orthodoxy Christian Theologians and Scholars of the History of Religion and Phenomenology of Religion. He made a great impact in Germany, after the World War I. With Das Heilige (The Idea of the Holy, 1917), he set the theological agenda for many years. His whole life work centred on understanding the nature of religion, and its divergent expression in the world religions. He was heir to the primary theological and philosophical tendencies in Germany at the end of the nineteenth century. He studied at Erlangen, Göttingen (1897-1914), became Privat-Dozent of Systematic Theology and later attained the status of Ausserordentlicher Professor in the same University, and at Breslau he was appointed to an official Chair (1914-1917), until he went to Marburg (1917-1929). One of the special interests in the last ten years of his life was the establishment at Marburg of a museum for the comparative study of religions, not as dead curiosities but as living faiths.